Allelopathic potential and systematic evaluation of secondary compounds in extracts from roots of Canavalia ensiformis by capillary electrophoresis - dos Santos, Sonia; de Moraes, Maria de Lourdes Leite; Rezende, Maria Olimpia de Oliveira (Eclética Química, 2007)
Organic extracts were obtained from roots of Canavalia ensiformis and evaluated for allelo- pathic potential on the germination of the weed seeds: Mimosa pudica, Cassia tora and Cassia occi- dentalis showing a strong allelopathic potential. After that, a systematic study of these crude extracts was made using specific protocols developed in capillary electrophoresis (CE) in order to determine some classes of secondary metabolites. Capillary electrophoresis protocols were highly specific, which makes it possible to identify 5 classes of compounds using the same crude extract samples and analyze them fartly. Some of the compounds identified show activity in the inhibition of seeds germination.